Agricultural Price Optimization: Balancing Farmer Sustainability with Consumer Affordability - Ankit Khandelwal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the intricate relationship between agricultural pricing strategies and their impact on farmer sustainability and consumer affordability. The article explores multiple dimensions of agricultural pricing, including market dynamics, core pricing models, supply chain economics, risk management strategies, government interventions, and future sustainability trends. The article reveals how modern digital technologies, climate change considerations, and evolving consumer preferences are reshaping traditional pricing approaches in agriculture. The article demonstrates that successful agricultural pricing strategies must balance multiple competing interests while adapting to emerging challenges such as weather volatility, market uncertainties, and sustainability requirements. Through detailed examination of various pricing models, risk management tools, and technological innovations, the article highlights the critical role of integrated digital solutions, data analytics, and sustainable practices in creating resilient agricultural pricing systems. The article emphasizes the importance of developing flexible, technology-driven pricing mechanisms that can simultaneously ensure fair returns for farmers, maintain food affordability for consumers, and promote long-term agricultural sustainability.
Keywords: Agricultural Price Optimization; Digital Agriculture Technologies; Supply Chain Economics; Sustainable Farming Systems; Risk Management Strategies